The impact of student-lecturer relationship on good decision-making and quality promotion in the institutions of higher education and training - Sundani, Ndivhuwo Doctor; Mamokhere, John (My University, 2021)
There is an increasing need to comprehend the impact of the student-lecturer relationship in the institutions of higher education and training (HET). Thus, this study determines the impact of the student-lecturer relationship on good decision-making and quality promotion in the institutions of HET in the South African context. The study argues that the relationship between student-lecturer is essential because it enhances the decision-making process and promotes quality education and training. The student-lecturer relationship has a significant impact on student academic performance in HET. Similarly, the student-lecturer relationship is key to students’ academic, social and emotional development. The Constructivism Theory of Learning (CTL) better understood and explained by Vygotsky (1978) & Piaget (1957) was used to raise critical analysis of the impact of the student-lecturer relationship on good decision-making and quality promotion in HET. Methodologically, the study have adopted a qualitative research approach in a form of document analysis. To further comprehend the relationship between students-lecturer on decision-making and quality promotion, the authors deployed Critical Discourse Analysis (CDA) which is best used in analysing qualitative data. Secondary data sources covering topics of student-lecturer relationship on decision-making and quality promotion were critically reviewed and synthesised. The study has found that the student-lecturer relationship plays a pivotal role in good decision-making in HET and enhances existing learning programmes. It was also discovered that a strong relationship between lecturers-students can help to increase competency among students. Student disengagement, disorganised lecturers, low motivation among students were found as common challenges that affect student-lecturer relationship. The study conclude by offering recommendations to enhance the student-lecturer relationship and its influence to improve decision-making and quality promotion in institutions of HET.
Journal article published in the journal of African Perspectives of Research in Teaching & Learning (APORTAL)-Vol 5 (2): (2021)
Keywords: Student-lecturer relationship; Decision-making; Quality promotion; Higher education; South Africa; Education, Higher -- South Africa; Constructivism (Education); Lectures and lecturing; College students -- South Africa